The Influence of Work Culture and Job Placement (Staffing) on the Work Productivity of Teachers and School Employees - Friyadi, Rio; Efriyanti, Liza (STIT Ahlussunnah Bukittinggi, 2025)
Organizational culture is a strategic instrument that plays a vital role in shaping the attitudes, behaviors, and loyalty of organizational members in support of achieving common goals. In responding to the challenges of globalization, organizations are required to adapt through effective human resource management, particularly by emphasizing the alignment between individual competencies and job placement. In the educational context, a thorough understanding of learning needs serves as the foundation for formulating appropriate staffing policies, enabling teachers and educational staff to work professionally and optimally in accordance with their areas of expertise. Competency-based educational management, proportional task distribution, fair reward systems, and effective leadership have been proven to significantly influence motivation, work discipline, and productivity. School leadership plays a crucial role in directing, motivating, and coordinating all components of educational institutions to ensure alignment with institutional vision and mission. This study employs a quantitative research approach to address the research problems through precise measurement of specific variables, producing conclusions that can be generalized beyond particular timeframes, situations, and data types, with an emphasis on quantitative data. The findings indicate that a conducive work environment, as implemented at the Al-Azhar Islamic Education Foundation, fosters organizational synergy that positively impacts both individual and institutional performance, thereby enabling educational objectives to be achieved effectively and efficiently.